Incidence of Reactionary Hemorrhage Among Patients After Open Hemorrhoidectomy at Surgical Unit of Tertiary Care Hospital (Medical Forum Monthly, 2021)
Objective: To determine frequency of delayed post haemorrhoidectomy bleedingStudy Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at Surgical Department of Mardan Medical Complex, Mardan from June 2017 to May 2019.Materials and Methods: Upon a sample of 336 consecutive patients (chosen via non-probability, consecutive sampling) of either gender, presenting with 3rd and 4th degree haemorrhoids and scheduled to undergo haemorrhoidectomy. After taking written informed consent, data was recorded onto a pre-structured questionnaire containing inquiries pertaining to basic biodata, sociodemographic details, disease history, inferences obtained from thorough examination (including proctoscopy) and follow up (after two weeks) findings (especially reactionary haemorrhage). The data obtained was analyzed using SPSS v. 21.0.Results: The mean age of the sample stood at 45.5 ± 6.85 SD and the gender distribution was largely equal. The incidence rate of reactionary haemorrhage was revealed to be 3.57% and stratification revealed reactionary haemorrhage did not vary with gender and age.Conclusion: After careful consideration, it can be concluded that the frequency of reactionary haemorrhage is low at the study setting and the findings are consistent across both genders and all age groups.